Conceptual design of a trust model for perceptual sensor data of autonomous vehicles - Halla-aho Lauri; Nigussie Ethiopia; Isoaho Jouni (Netherlands, 2022)
This paper presents a conceptual trust model for the perceptual sensor data of autonomous vehicles to improve their reliability and safety of operation. In particular, the model aims to ensure the trustworthiness of the data used in the automated decision-making processes of vehicles. The presented model forms a comprehensive view of factors that affect trust in the perceptual sensor data. These factors, namely environment, operation, security, and technical limitations, further cover a number of related trust parameters used to evaluate trust values. Each parameter is evaluated using Dempster-Shafer theory using a trust-distrust frame. Mass values are based on instantaneous sensor data and sensor behaviour tested under similar circumstances. As a result, this model is viable for use in conjunction with data fusion and decision-making to improve their reliability by enabling the tracking of the development of sensor trustworthiness.
The 12th International Conference on Ambient Systems, Networks and Technologies (ANT) / The 4th International Conference on Emerging Data and Industry 4.0 (EDI40) / Affiliated Workshops